High performance computing in science and engineering - Haas, P. W.; Resch, M. M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
High performance computing has gradually shifted from the realm of research into development and partially even into the production cycles of industry. High performance computers therefore have to be integrated into production environments that demand the simultaneous solution of multidisciplinary physics problems. Supercomputer centers can learn from these new challenges imposed by industry. The concepts of workflow and production cycle open up a new horizon for integrating systems and software into what is called a distributed 'Teraflop-workbench' approach. Terascale storage and communication infrastructures eventually needed to support such an environment.